PERUBAHAN MINDSET MENGAJAR DALAM MENYIAPKAN PENDIDIK YANG PROFESIONAL DALAM PERSAINGAN DI ERA MEA - ROMENAH ROMENAH (Universitas Pamulang, 2018)
AbstractThe National Education System has grown so rapidly over time. A variety of efforts have been made to build every prosperous, dignified Indonesian human being, so that the quality of Indonesian thinking is progressing. The ASEAN Economic Community which has been launched since 2015 has resulted in free competition, both in trade, employment, and there is free competition for educators in ASEAN countries. Besides that, Indonesian education is faced with challenges and developments in the times, where the culture between ASEAN countries has no limits, this is the challenge faced when implementing the Asean Economic Comunity (ASEAN Economic Community) MEA. Indonesia as a country in the ASEAN region must prepare domestic educators to have professionalism and character so that they can compete with the AEC. Educators must be aware of the essence of the existence of their profession, continue to struggle to make changes in order to realize professionalism with noble character. Efforts made in preparing professional educators to face the challenges of the AEC must touch the most fundamental aspects of changing their competencies, namely the mindset. A student must be more advanced and innovative in developing his learning so that he can change the mindset of students to do agent of change. Through this mindset educators will become professional and characterized so that they can compete and compete in the MEA era. Keywords: MEA, Changes in Mindset, Professional Educators